Opera omnia Desiderii Erasmi Roterodami Ordinis Septimi Tomus Sextus - Bateman, John J. (Huygens instituut/Brill, 1997)
This twenty-fourth volume in Erasmus's Opera omnia contains the Paraphrases on Hebrews-3 John. The Paraphrases belong to the seventh of the nine 'ordines' into which Erasmus's works are divided. For this division, laid down by Erasmus himself, see General introduction in ASD I, I, pp. x, xvii-xviii, and C. Reedijk, Tandem bona causa triumphat. Zur Geschichte des Gesamtwerkes des Erasmus von Rotterdam. Vortrage der Aeneas-Silvius-Stiftung an der Universitat Basel, XVI, Basel/ Stuttgart, 1980, pp. 12 sqq., 21-22. This volume containing the last part of the Paraphrases (ASD VlI,6) is the first to appear in 'ordo' VII; the Paraphrases on the other books of the New Testament (ASD VII, 1-5) will be published later. The order of publication depends on when the respective volumes are finished. For the names of the members of the Editorial Board as from 1 November 1996 see the back of the title page. The Editorial Board and the editor of the present volume are grateful to all libraries that kindly put photostats, microfilms, and bibliographical material at their disposal.